2019
DOI: 10.1101/2019.12.12.874701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assembly of a young vertebrate Y chromosome reveals convergent signatures of sex chromosome evolution

Abstract: Heteromorphic sex chromosomes have evolved repeatedly across diverse species. Suppression of recombination between X and Y chromosomes leads to rapid degeneration of the Y chromosome. However, these early stages of degeneration are not well understood, as complete Y chromosome sequence assemblies have only been generated across a handful of taxa with ancient sex chromosomes. Here we describe the assembly of the threespine stickleback (Gasterosteus aculeatus) Y chromosome, which is less than 26 million years ol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 112 publications
3
21
0
Order By: Relevance
“…High-quality genome assemblies of sex chromosomes are becoming more available (Liu et al 2019;Peichel et al 2019). An assembly of the neo-Y chromosome of Drosophila miranda showed that the neo-Y chromosome has expanded and many of the genes have been amplified to high copy number (Bachtrog et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…High-quality genome assemblies of sex chromosomes are becoming more available (Liu et al 2019;Peichel et al 2019). An assembly of the neo-Y chromosome of Drosophila miranda showed that the neo-Y chromosome has expanded and many of the genes have been amplified to high copy number (Bachtrog et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many chr. Un contigs that were not placed in the v. 4 genome assembly may be represented in the v. assembly if they were contained completely within a PacBio Canu contig (Peichel et al 2019). To test this, we used BLAT to align the 3378 chr.…”
Section: Closing Gaps In the Reference Assemblymentioning
confidence: 99%
“…These annotations combined evidence from multiple RNA-seq transcriptomes, all predicted Ensembl protein sequences (release 95), and ab inito gene predictions from SNAP (v. 2006-07-28) (Korf 2004) and Augustus (v. 3.3.2) (Stanke et al 2006). MAKER was run over three rounds using the RNAseq transcriptomes and methods previously described (Peichel et al 2019).…”
Section: Genome Annotationmentioning
confidence: 99%
See 2 more Smart Citations